Horizon-T extensive air showers detector system operations and performance - Beznosko, Dmitriy; Batyrkhanov, А.; Beremkulov, Т.; Duspayev, A.; Iakovlev, A.; Makhataeva, Z.; Yelshibekov, K.; Yessenov, M.; Beisembaev, R.U.; Zhukov, V.V. (38th International Conference on High Energy Physics, 2016)
“Horizon-T” is an innovative detector system located at Tien Shan high-altitude Science Station (TSHASS) at approximately 3340 meters above the sea level. It consists of eight detection points separated by the distance up to one kilometer that can measure time characteristics of the Extensive Air Showers (EAS) and record signal shapes with time resolution of ~10 ns. It was constructed to register EAS in the energy range above 1016 eV coming from a wide range of zenith angles (0o - 85o). The system includes both the plastic scintillator particle detectors as well as the Vavilov - Cerenkov radiation detectors subsystem to observe the Cerenkov light from the EAS in the atmosphere directly. The time resolution and signal shape analysis capabilities of the detection points are used to study EAS development in the atmosphere. The development of the EAS is a process that can be studied both spatially and temporally. For the spatial part, a distributed network of detection points is required. For the time part, a signal shape must be recorded and analysed at each point with time resolution on the order of ~10 ns. In this paper, the current system description and performance level are described. Additionally, the latest data examples showing the unusual EAS examples above 1017 eV are included.